Indicators of Sex Trafficking in Online Escort Ads, 7 U.S. states, 2013-2020 - Lugo-Graulich, Kristina ([Verlag nicht ermittelbar], 2024)
With the aim of improving precision in sex trafficking victim identification and investigations, this exploratory, mixed-methods study had two objectives: 1) To investigate whether there are indicators that differentiate online escort ads related to sex trafficking from ads for non-trafficked sex work, and 2) if so, to determine which indicators are most likely to predict whether the ad represents a case of sex trafficking. Research activities took place over a three-year period (2018-2021). First, the research team developed the set of indicators to test based on previous literature and insight from three sets of focus groups: law enforcement and victim advocates, trafficking survivors, and non-trafficked sex workers. Focus groups also provided insight into indicators that may be misinterpreted and into how advertising practices have changed, especially since the passage of FOSTA (Allow States and Victims to Fight Online Sex Trafficking Act) and SESTA (Stop Enabling Sex Traffickers Act), and the shutdown of Backpage.com by the FBI. Second, the researchers collected investigative file information on closed cases involving escort ads from several locations in the United States, using phone numbers identified in each case to pull associated ads missing from case files from one of three web scraper databases (the MEMEX archive and the active TellFinder and HTI Labs' Law Enforcement Assistant for Dismantling Sex Trafficking Networks (LEADS) web scrapers). The final dataset includes 318 closed commercial sex and massage cases investigated in seven states, with 1,586 unique associated ads covering 35 U.S. states and Ontario, Canada. Researchers also pulled additional ads not present in the case files from the scraper archives to conduct three case studies of trafficking movement patterns, network management, and advertising structures to provide context for the hypothesis test results. Finally, after analysis of the ad- and case-level data, a second round of focus groups was conducted to obtain each group's responses to the results, advice on interpretation, and input on recommendations. The case-level (DS1) and ad-level (DS2) quantitative data are currently available in this collection. The qualitative data will be released at a future date. Please refer to the ICPSR README and the study documentation for more information about the files.